2021
DOI: 10.1101/2021.02.03.429495
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular dynamics simulation study reveals effects of key mutations on spike protein structure in SARS-CoV-2

Abstract: SARS-CoV-2 has been spreading rapidly since 2019 and has produced large-scale mutations in the genomes. Differences in gene sequences may lead to changes in protein structure and traits, which would have a great impact on the epidemiological characteristics. In this study, we selected the key mutations of SARS-CoV-2, including D614G and A222V of S protein and Q57H of ORF3a protein, to conduct molecular dynamics simulation and analysis on the structures of the mutant proteins. The results suggested that D614G i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 61 publications
(91 reference statements)
1
3
0
Order By: Relevance
“…From the 50 ns molecular dynamics simulation carried out in GROMACS, the complex between the ACE2 receptor and the Spike protein variant of B.1.617 was found to be most stable considering its structural deviation, local area flexibility, state of folding, and susceptibility to disruption by solvents ( Fig 10 ). These findings coincide with those reported in other studies and the enhanced Spike protein stability of the B.1.617 is likely to contribute to the efficiency of transmission of SARS-CoV-2 [ 88 90 ].…”
Section: Discussionsupporting
confidence: 92%
“…From the 50 ns molecular dynamics simulation carried out in GROMACS, the complex between the ACE2 receptor and the Spike protein variant of B.1.617 was found to be most stable considering its structural deviation, local area flexibility, state of folding, and susceptibility to disruption by solvents ( Fig 10 ). These findings coincide with those reported in other studies and the enhanced Spike protein stability of the B.1.617 is likely to contribute to the efficiency of transmission of SARS-CoV-2 [ 88 90 ].…”
Section: Discussionsupporting
confidence: 92%
“…49,50 Lon et al observed mutant models (D614G, A222V, N501Y, T716I, S982A, D1118H) of SARS-CoV-2 spike protein are more stable and more compact, as the mutant models displayed less RMSD and Rg values in molecular dynamic simulation study. 49 Another study reported that W80R mutation in kinase B protein targeting ovarian cancer is more stable as it has less RMSD than wild-type model. 50 Khan et al reported that mutant models exhibit more intramolecular hydrogen bonds than wild-type of Rab5a protein.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have performed molecular dynamic simulation analysis to observe effect of point mutations on protein 49,50 . Lon et al.…”
Section: Discussionmentioning
confidence: 99%
“…It was found in 53.8% of all uploaded sequences in November 2020 and assumed to influence viral transmissivity and antigenicity (Hodcroft et al, 2020; Bartolini et al, 2020). The mutation might, however, enhance the ability of the protein to interact with the environment (Lon et al, 2021). The M gene is also featured by a frequent mutation - C26801G (L93L) is found in 21.82%, which constitutes between 53.4% and 43.2% of all uploads from November 2020 to December 2020.…”
Section: Discussionmentioning
confidence: 99%